(untitled) (REMUNOM, 2025)
The use of electric energy worldwide has intensified throughout human history. In Brazil, most of the electricity produced comes from hydroelectric plants. However, with the episodes of water shortages that have been recorded, the environmental impacts caused by the implementation of hydroelectric plants, and the high cost of electricity bills, the search for ecological and economically viable alternatives has become necessary. In this context, photovoltaic solar energy stands out as a form of energy derived from an inexhaustible natural resource, which does not harm the environment and has great generation potential throughout Brazil. However, it is still underutilized due to the high initial investment required for its implementation. Therefore, this study aims to analyze, through the methods of Net Present Value (NPV), Internal Rate of Return (IRR), and Discounted Payback, the economic viability of implementing a photovoltaic solar system in a residence in the city of Teófilo Otoni – MG. For this purpose, a budget for a photovoltaic solar system appropriate to generate the energy used by the residence was prepared, based on the consumption history of the last 13 months. For the economic feasibility analysis, the NPV, IRR, and Payback methods were applied, comparing in both methods the amounts paid to CEMIG in the last year with the values quoted by the solar energy company. The results indicated that, for the residence under study, the use of photovoltaic solar energy is economically viable, considering a Minimum Attractive Rate of Return of 0.57% per month and a payback period of 5 years (60 months), resulting in an NPV of R288.48, an IRR of 0.656% per month, and a Payback of 59 months.